THE USE OF MIND MAPPING TECHNIQUE IN WRITING DESCRIPTIVE TEXT - Sakkir, Rini Isnaeni; Korompot, Chairil Anwar; Sofyan, Ryan Rayhana (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study is a pre-experimental research that aims to find out the use of mind mapping to improve students’ writing skills. The participants were the students of VIII-3 MTsN 2 Makassar for the academic year 2021/2022 with as many as twenty-two students. Cluster random sampling was used as the way of selecting the sample and a writing test (descriptive text) was administered as the way of collecting data. The result showed that the score of students’ writing skill tests was improving after conducting mind mapping in the writing class. The mean score of students’ writing tests before and after applying the mind mapping technique improved (53.18 to 75.27). It means that the student’s writing skills can be improved by using mind mapping as a teaching strategy in writing class.